Conditions of Mainland China’s Island Ecosystems and Associated Influencing Factors: Integrated Assessment of 42 Typical Island Ecosystems - Ma, Zhiyuan; Yu, Weiwei; Zhang, Wanting; Ge, Feiyang; Chen, Bin; Hu, Wenjia; Zhang, Dian; Liao, Jianji; Huang, Hao; Sun, Yuanmin; Huang, Haiping (Frontiers in Marine Science, 2022)
Although China possesses a large number of islands, knowledge of their overall ecological condition is limited on a national scale. Accordingly, this study developed a comprehensive and quantitative island ecosystem assessment framework that incorporates environmental quality, biological structure, and landscape patterns. The framework was applied to 42 typical, representative islands within China’s coastal regions, including different climatic zones, area sizes, populations, and substratum lithologies. Results showed that the value range of the comprehensive index of island ecosystem condition (CIisland) was significant (from 52.33 to 89.53, 71.72 average), and 85.4% of islands scored either “high” or “good,” indicative of their exceptional condition. However, conditions varied among different island components, indicating different challenges. Environmental quality index (Ienv) values ranged from 60.70 to 94.80 (79.72 average), where primary threats were seawater nutrient pollution, petroleum, and marine organism metal contamination. Biological structure index (Ibio) values ranged from 43.50 to 89.40 (66.10 average), where primary threats were vegetation destruction and a reduction in marine biodiversity within intertidal and subtidal zones. Landscape pattern index (Iland) values varied significantly (from 6 to 100, 72.36 average), where a key characteristic of highly developed islands was low natural landscape (vegetation) coverage. Conditions also varied among island climate zones, lithologies, area sizes, and levels of human habitation. Additionally, island ecosystem conditions were influenced by both natural and anthropogenic factors as well as area size, population, and GDP. Although distance to the mainland significantly correlated to (Ibio), and (CIisland), these parameters did not significantly correlate to (Ienv), which might be explained by that environmental quality was generally conditional on large-scale environments. This assessment is intended to provide a holistic perspective on island conditions in China while identifying key challenges and associated driving factors, which will greatly aid in establishing island-specific sustainable management practices.